ANALISIS PRODUKSI DAN EFISIENSI IKAN LAUT NELAYAN BAGAN MESIN DI KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Mariani, Nevi; Aimon, hasdi; Sentosa, Sri Ulfa (Program Studi Magister Ilmu Ekonomi, 2014)
South coast most of the territory is along the coast has the potential tomake the fishery once the prime mover (prime mover) South Coast economy.Support potential and natural conditions is an area big enough assets to driveeconomic growth in the South Coast region. Production of marine fish fishingcharts are many factors that influence engine. Among them is the amount of labor,fishing experience, working capital, mileage and length of fishing. The estimationresults of multiple regression equation is obtained as follows:LogY = 0,264LogX1 - 0,189LogX2 +0,306LogX3 + 0,97LogX4 - 0,315LogX5.R-squared value of marine fish production equation is equal to 0.382. This showsthe contribution of independent variables on the dependent variable is equal to 38percent. The use of factors of production the amount of labor (X1), the fishingexperience (X2), working capital (X3), mileage (X4) and duration of fishing (X5)is efficient.Keyword: production, Efficiency and fishing chart engine